1991
DOI: 10.1002/jlac.199119910148
|View full text |Cite
|
Sign up to set email alerts
|

Synthetic and stereochemical studies on phthalideisoquinoline hemiacetals

Abstract: The two new phthalideisoquinoline hemiacetals rac‐egenine (3) and rac‐corytensine (4) are prepared by stereoselective DIBAL reduction of rac‐bicuculline (1) and rac‐adlumidine (2), respectively. The identity of egenine (3) with decumbensine as well as of corytensine (4) with epi‐α‐decumbensine and humosine A is postulated. The configuration around the anomeric center in natural (+)‐egenine (3), (+)‐corytensine (4) and (−)‐narcotine hemiacetal (7) is deduced as (7′S), (7′R) and (7′R), respectively.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
2
0

Year Published

1991
1991
2020
2020

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(2 citation statements)
references
References 18 publications
0
2
0
Order By: Relevance
“…The early attempt to generate (±)-egenine was completed by LiAlH 4 reduction of (±)-bicuculline, which resulted in only one anomeric hemiacetal . It was reported that the anomeric form was likely to be stabilized by an intramolecular hydrogen bond, and the absolute configuration of (+)-egenine at C-7′ was then defined as R . This structural assignment was later verified by single-crystal X-ray crystallography of (−)-egenine, and the assumed hydrogen bond was observed .…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The early attempt to generate (±)-egenine was completed by LiAlH 4 reduction of (±)-bicuculline, which resulted in only one anomeric hemiacetal . It was reported that the anomeric form was likely to be stabilized by an intramolecular hydrogen bond, and the absolute configuration of (+)-egenine at C-7′ was then defined as R . This structural assignment was later verified by single-crystal X-ray crystallography of (−)-egenine, and the assumed hydrogen bond was observed .…”
mentioning
confidence: 99%
“…The absolute configurations of C-1 and C-9 were initially determined by chemical degradation studies, yet the configuration of the C-7′ anomeric center was unreported for some time . The early attempt to generate (±)-egenine was completed by LiAlH 4 reduction of (±)-bicuculline, which resulted in only one anomeric hemiacetal . It was reported that the anomeric form was likely to be stabilized by an intramolecular hydrogen bond, and the absolute configuration of (+)-egenine at C-7′ was then defined as R .…”
mentioning
confidence: 99%